Effective ring - Zabavsky, B.V.; Kuznitska, B.M. (Algebra and Discrete Mathematics, 2014)
In this paper we will investigate commutative Bezout domains whose finite homomorphic images are semipotent rings. Among such commutative Bezout rings we consider a new class of rings and call them an effective rings. Furthermore we prove that effective rings are elementary divisor rings.